Sport tourism development: Cultural, economic and political perspectives - Homafar, Fazele; Honari, Habib; Heidary, Akhbar (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
Sport tourism is a new concept in the world having the most growth in tourism industry. Many of countries enjoy an appropriate status with respect to sport tourism and,accordingly,contribute directly to their nation`s economic prosperity. Hence, the goal of this research is comparison and survey of tourism managers, interest managers and tourisms' ideas about creation of sport tourism-induced employment and income in Mazandaran-Iran. The tool of this research is a researcher-made five scale likert questionnaire. The questionnaire reliability and the coefficient validity were confirmed by experienced professors and with (α = 0.82),respectively. Finally, The data analysis carried out using the SPSS software and χ2 statistic test.The results show that job creation (χ ‗ 4.360, p‗ 0.35) and income production (χ2 ‗1.633, p‗ 0.80) were previously at a minimum However, the role of tourism industry development is believed to create jobs (χ2 ‗ 9.740 ,p‗ 0.04)and income(χ2 ‗ 5.224,0.51). Compared with other studies ,the present research indicates that future sport tourism industry influences job and income production in the regions hosting the sport events provided that the sport tourism industry and its respective infrastructures are well-developed .